Cystic lesions of pancreas: challenges in diagnosis and management - Bohara, S; Tamang, TY; Maharjan, DK; Shrestha, SK; Thapa, PB (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Pancreatic cysts are common (2.5%). Cystic neoplasms represent 10% of cystic lesions and 1% of pancreatic tumors. However, it is difficult to differentiate benign cyst from malignant cystic lesions preoperatively.Objective: To study the cases of pancreatic cystic lesion who underwent various forms of pancreatic resection.Materials and Methods: Nine cases of pancreatic cystic lesion who presented to Kathmandu Medical College Teaching Hospital, Surgical Unit 3 within December 2014- November 2015 were evaluated. Four pancreatic cysts who underwent resection are discussed whereas not managed with resection are excluded.Results: There were 4 cases of pancreatic cyst who underwent pancreatic resection. First case underwent pancreaticoduodenectomy for pancreatic mucinous cystadenoma. However histopathological examination revealed a serous cystadenoma. In second case, pancreatic neck lesion suspected to be mucinous cystadenoma or pseudocyst in MRCP, with negative malignant cells in EUS guided FNAC underwent Central pancreatectomy and was found to be serous cystadenoma. The third case with suspected pseudocyst underwent Pancreaticoduodenectomy after a 3X2 cm2 cystic mass was felt at the posteroinferior side of pancreatic head and malignancy was suspected intraoperatively . HPE report was mucinous cystadenoma. The fourth case with pancreatic pseudocyst at tail with duct calculi and chronic pancreatitis underwent distal pancreatectomy with splenectomy with Frey’s procedure.Conclusion: Management of pancreatic cystic lesion is challenging. Though radiological imaging has limited role in accurate diagnosis, endoscopic ultrasound may be of some benefit.